Identification of a rare coding variant in complement 3 associated with age-related macular degeneration - Zhan, Xiaowei; Larson, David E; Wang, Chaolong; Koboldt, Daniel C; Sergeev, Yuri V; Fulton, Robert S; Fulton, Lucinda L; Fronick, Catrina C; Branham, Kari E; Bragg-Gresham, Jennifer; Jun, Goo; Hu, Youna; et al. (Nature genetics, 2013)
Goncalo Abecasis and colleagues report identification of a rare coding variant in the complement 3 gene that is associated with age-related macular degeneration. Macular degeneration is a common cause of blindness in the elderly. To identify rare coding variants associated with a large increase in risk of age-related macular degeneration (AMD), we sequenced 2,335 cases and 789 controls in 10 candidate loci (57 genes). To increase power, we augmented our control set with ancestry-matched exome-sequenced controls. An analysis of coding variation in 2,268 AMD cases and 2,268 ancestry-matched controls identified 2 large-effect rare variants: previously described p.Arg1210Cys encoded in the CFH gene (case frequency ( f case ) = 0.51%; control frequency ( f control ) = 0.02%; odds ratio (OR) = 23.11) and newly identified p.Lys155Gln encoded in the C3 gene ( f case = 1.06%; f control = 0.39%; OR = 2.68). The variants suggest decreased inhibition of C3 by complement factor H, resulting in increased activation of the alternative complement pathway, as a key component of disease biology.